Primary School Teachers’ Creative Self-Perception and Beliefs on Teaching for Creativity - Eva Izquierdo-Sanchis; Yolanda Echegoyen-Sanz; Antonio Martín-Ezpeleta (Education Sciences)
The recent Spanish education law, LOMLOE, highlights the importance of integrating creativity into all subjects in Primary Education. Teachers play a crucial role in this process, yet often lack adequate training, and research on their beliefs about creativity remains limited. This study examines the creative self-perception of Spanish in-service Primary Education teachers and their beliefs about teaching for creativity, using two previously validated instruments. The findings reveal a moderate self-perception of creativity across various domains, with significant gender differences, as well as a positive attitude towards teaching for creativity. No significant differences were found based on age or years of teaching experience, suggesting a static nature within the teaching profession, misaligned with emerging educational challenges. The correlational analysis indicates a positive relationship between creative self-perception and different dimensions of teaching for creativity, highlighting the importance of support from educational institutions. These findings advocate for continuous teacher training and resources to strengthen creativity-focused teaching practices.